Electrospun PMMA polymer blend nanofibrous membrane: electrospinability, surface morphology and mechanical response - Lee, Jacky Jia Li; Andriyana, Andri; Ang, Bee Chin; Huneau, Bertrand; Verron, Erwan (IOP Publishing, 2018)
The present work focuses on the electrospinning ability, the evaluation of resulting surface morphology and mechanical response of PMMA polymer blend nanofibrous membranes. For this purpose, electrospinning ability of PMMA polymer blend is firstly investigated by exploring various set of electrospinning parameters. From the evaluation of surface morphology of the resulting electrospun membranes, the optimum parameters are identified. Using these optimum parameters, tensile specimens are subsequently produced. Three deformation modes are considered: monotonic tensile test, cyclic test with increasing maximum strain and cyclic-relaxation test. Morphological analysis shows that the optimized tensile specimens are initially isotropic on the plane. The mechanical test results highlight the strong inelastic responses of the materials, which include inelastic strain and time-dependent behavior characterized by stress relaxation. Finally, in situ tensile test outcomes suggest that strain-induced fiber re-orientation took place.